Риск - это наша работа: роман / Сергей Самаров - Самаров Сергей Васильевич (Спецназ, 2004)
Экземпляры: Ф-2 (20220505) / Инвентарный номер: 97375 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: С 17 / ББК: 84(2=411.2)6-4